Petroclival Chondrosarcoma: A Multicenter Review of 55 Cases and New Staging System. Issue 7 (August 2016) - Carlson, Matthew L.; O'Connell, Brendan P.; Breen, Joseph T.; Wick, Cameron C.; Driscoll, Colin L.; Haynes, David S.; Thompson, Reid C.; Isaacson, Brandon; Gidley, Paul W.; Kutz, J. Walter; Van Gompel, Jamie J.; Wanna, George B.; et al.
Abstract : Objective: To analyze clinical outcomes after treatment of petroclival chondrosarcoma and to propose a novel staging system. Study Design: Retrospective case review, 1995 to 2015. Setting: Multicenter study. Patients: Consecutive patients with histopathologically proven petroclival chondrosarcoma. Intervention(s): Microsurgery, endoscopic endonasal surgery, radiation therapy, observation. Main Outcome Measures: Disease- and treatment-associated morbidity, recurrence, mortality. Results: Fifty-five patients (mean age 42 years; 56% women) presenting with primary or recurrent petroclival chondrosarcoma were analyzed. The mean duration of follow-up was 74 months. Among 47 primary cases, the most common presenting symptoms were headache (55%) and diplopia (49%) and the mean tumor size at diagnosis was 3.3 cm. Subtotal resection was performed in 33 (73%) patients and gross total resection in 12 (27%). Adjuvant postoperative radiation was administered in 30 (64%) cases. Preoperative cranial neuropathy improved in 13 (29%), worsened in 11 (24%), and remained stable in 21 (47%) patients; notably, 11 preoperative sixth nerve palsies resolved after treatment. Nine recurrences occurred at a mean of 42 months. The 1-, 3-, 5- and 10-year recurrence-free survival rate for all 45 patients who underwent primary microsurgery with or without adjuvant radiation therapy was 97%, 89%, 70%, and 56%, respectively. Higher tumor stage, larger categorical size (<4 versus ≥4 cm), lack of adjuvant radiation, and longer duration of follow-up were associated with greater risk of recurrence. The overall mortality rate was 2% for patients presenting with primary disease. Analyzing the cohort of 17 cases with 20 recurrences, 3 received salvage surgery alone, 5 radiation therapy alone, 11 multimodality treatment, and one patient has been observed. Tumor control was ultimately achieved in 15 of 17 patients with recurrent disease. One patient (6%) with grade 3 petroclival chondrosarcoma died as a result of rapidly progressive disease within 6 months of salvage treatment. The overall mortality rate was 6% for patients with recurrent disease. Conclusion: Gross total or subtotal resection with adjuvant radiation provides durable tumor control with minimal morbidity in most patients. Surgery may improve preoperative cranial nerve dysfunction, particularly in the case of cranial nerve 6 paralysis.